2015
DOI: 10.1159/000438967
|View full text |Cite
|
Sign up to set email alerts
|

miR-584 Suppresses Invasion and Cell Migration of Thyroid Carcinoma by Regulating the Target Oncogene <b><i>ROCK1</i></b>

Abstract: Background: Uncovering the target gene of miR-584 to control thyroid carcinoma (TC) invasion and migration is of central importance in the diagnosis, treatment, and prognosis of TC. To validate whether miR-584 has a tumor-suppressive role in thyroid cancer cells by targeting ROCK1, a series of experiments were conducted to figure out the mechanism of action of miR-584. Material and Methods: Migration analyses and cell proliferation assays were performed using miR-584-transfected cells. The expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
0
35
1
Order By: Relevance
“…Additionally, miR-584 is an independent prognostic factor for the outcome in neuroblastoma patients (38). Downregulation of miR-584 was also observed in clear cell renal cell carcinoma (21), thyroid carcinoma (22,23) and glioma (24). These findings suggested that aberrant expression of miR-584 is a potential prognostic factor in these cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, miR-584 is an independent prognostic factor for the outcome in neuroblastoma patients (38). Downregulation of miR-584 was also observed in clear cell renal cell carcinoma (21), thyroid carcinoma (22,23) and glioma (24). These findings suggested that aberrant expression of miR-584 is a potential prognostic factor in these cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Ueno et al revealed that miR-584 overexpression decreased cell motility in clear cell renal cell carcinoma (21). Moreover, Orlandella et al showed that resumed expression of miR-584 inhibited the migration and invasion of thyroid carcinoma cells and induced their resistance to apoptosis (22,23). Wang et al indicated that miR-584 reexpression repressed cell groWTh, migration, invasion and vasculogenic mimicry of glioma (24,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is easy to collect miRNAs from serum samples due to their stable form which can resist RNase digestion and other harsh conditions [13,14]. Moreover, miRNAs have been reported to regulate gene expression at the post-transcriptional level by binding to the 3'-untranslated region (3'-UTR) of targeted mRNAs [15], which might contribute their potential role in the progression of human cancers including CCA [16][17][18][19]. For example, Wang et al [20] suggested that microRNA-26a might play a crucial role in the diagnosis and prognosis of CCA, and provide a novel therapeutic target for this malignancy.…”
Section: Introductionmentioning
confidence: 99%